2020
DOI: 10.3390/ijerph17072535
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Good Affordable Food Intervention for Adults with Low Socioeconomic Status and Small Incomes

Abstract: Good Affordable Food (GAF) is a small-group nutrition education intervention for adults with low socioeconomic status and small incomes. It aims to empower participants to save money on groceries and consume healthier diets. This paper reports the short-term and longer-term effects on behavioural determinants and self-reported behavioural changes. A quasi-experimental control group design was applied with a baseline measurement, a post-test immediately after the intervention, and a follow-up measurement after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
5
0
11
Order By: Relevance
“…In "Considering Health Literacy, Health Decision-Making, and Health Communication in the Social Networks of Vulnerable New Mothers in Hawai'i", Sentell and colleagues [61] consider the importance of health literacy in the decision-making networks of new mothers, and how to measure this shared capacity using social network analyses. Bessems et al [62] created and tested small-group nutrition education intervention for adults with low socioeconomic status and small incomes in "The Effectiveness of the Good Affordable Food Intervention for Adults with Low Socioeconomic Status and Small Incomes".…”
Section: Interpersonal Level: Social Networkmentioning
confidence: 99%
“…In "Considering Health Literacy, Health Decision-Making, and Health Communication in the Social Networks of Vulnerable New Mothers in Hawai'i", Sentell and colleagues [61] consider the importance of health literacy in the decision-making networks of new mothers, and how to measure this shared capacity using social network analyses. Bessems et al [62] created and tested small-group nutrition education intervention for adults with low socioeconomic status and small incomes in "The Effectiveness of the Good Affordable Food Intervention for Adults with Low Socioeconomic Status and Small Incomes".…”
Section: Interpersonal Level: Social Networkmentioning
confidence: 99%
“…According to the results of this study, it is speculated that under a relatively low socioeconomic status, the reason why personal monthly living expenses have a significant impact on their nutritional status may be due to the differences in their purchasing power resulting in significant differences in the nutritional substances they choose. Currently, research has shown that guiding low-income people to choose nutritious and affordable foods can reduce the difference in nutritional status ( 42 ). The promotion of such intervention measures may have significant benefits in improving the nutritional status of low-income elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Practical and straightforward messages may help communities adopt new nutritional information [ 64 ]. Health practitioners should adequately promote the nutrition guidelines by including locally available food [ 65 ] and pricing information [ 66 ] during all contact with mothers and young children, such as antenatal and postnatal care. Nutrition counselling and education should occur in multiple settings, involve local human resources, and reach out to mothers regardless of their socioeconomic backgrounds to ease disparities.…”
Section: Discussionmentioning
confidence: 99%